2022
DOI: 10.56499/jppres21.1208_10.2.303
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitis gracilis Wall (gagatan harimau) in the recovery of gastrocnemius muscle cells and cytochrome c expression of Mus musculus

Abstract: Context: Physical exercise with maximum intensity to fatigue can cause impaired immunity. Gastrocnemius muscle damage is found in eccentric activities in sports. Vitis gracilis has been proven as a healing agent for degenerative diseases. Aims: To determine whether the V. gracilis Wall extract can recovery of gastrocnemius muscle cells of Mus musculus through reduced inflammatory cells and cytochrome c expression. Methods: The studies turned into performed in 5 groups of remedies withinside the study. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The leaves of Vitis gracilis contain alkaloids, flavonoids, saponins, tannins and glycosides 2 . As medicinal ingredients, phenols, organic acids, glycosides, amino acids, flavonoids and other chemical as antioxidant constituents of Vitis gracilis can be developed 2,3 . Another study using other herbs showed that dietary curcumin ameliorated radiation-induced pulmonary fibrosis and increased survival in mice without interfering with radiation-induced tumor cell killing 12,13 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The leaves of Vitis gracilis contain alkaloids, flavonoids, saponins, tannins and glycosides 2 . As medicinal ingredients, phenols, organic acids, glycosides, amino acids, flavonoids and other chemical as antioxidant constituents of Vitis gracilis can be developed 2,3 . Another study using other herbs showed that dietary curcumin ameliorated radiation-induced pulmonary fibrosis and increased survival in mice without interfering with radiation-induced tumor cell killing 12,13 .…”
Section: Discussionmentioning
confidence: 99%
“…The cells of the lungsʼ alveoli are very thin (0.2-0.5 m) and arranged in such a way that alveolar sacs form 20 . When stretched, the entire lung alveoli cells reach (a width of 70-80 m 2 ). An interalveolar wall (septum) connects the alveolar sacs and is made up of two layers: Simple squamous epithelium and connective tissue 20,21 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations